Proyecto socioeducativo para la prevención del maltrato infantil con padres, madres y educadoras del centro infantil Niñito Jesús. - Chanatasig Herrera, Johana De Los Ángeles (2017)
This research deals with the issue of child abuse in children who make up the Niñito Jesús Infantile Center in the canton Latacunga, where the experience of parents and educators is reported through educational workshops on the subject of abuse and its effects, contextualizing this problem, Its consequences and the psychosocial factors, to undertake an intervention with content that potentially contributes to the direct beneficiaries that are precisely the educators, the parents and the children. In order to meet the objectives set out, a methodological tool has been provided to guide and guide preventive work by educators, which is why workshops are designed for teaching work with families to prevent child maltreatment. In the development of the project, the results obtained through the application of group work techniques with parents and educators were mentioned, which generated the information collection and favored the dynamics of the orientation and accompaniment process to the educators of the children's center. The design and methodological proposal of workshops relate the experiences developed in the training for parents and teachers, which constitute the contribution of the proposal. Finally, the conclusions and recommendations are the positive contribution of this intervention conceptualized in the workshops, in order to improve the behavioral attitudes of parents, with a significant impact on the problem of child maltreatment and its psychosocial aspects, thus promoting the execution of future interventions focused on interdisciplinary work.